Pengaruh Penggunaan Media Blok Pecahan Terhadap Minat Belajar Pada Mata Pelajaran Matematika Siswa Kelas III SD Kompleks Lariang Bangi Kecamatan Makassar Kota Makassar - Aras, Latri; Syawaluddin, Ahmad; Amrah, Amrah (Universitas Negeri Makassar, 2019)
Through this study, the objectives to be achieved are to (1) describe the extent to which: (a) the interest in learning elementary school mathematics through the use of Fraction Block Media, (b) student responses, and (c) implementation using fraction block media (2) see the effectiveness of the use of Block Fraction media, and (3) publication of scientific articles dijurnal national accreditation or international journals. The research design that will be used is a quasi experimental research design with a pretest-posttest control group design. The study population was Class III students at SD Kompeks Lariang Bangi consisting of 3 schools, namely Lariang Bangi 1 Elementary School, Lariang Bangi 2 Elementary School, and Lariang Bangi 3 Elementary School with two classes of samples. The research instruments consisted of (1) Questionnaire Interest in Elementary Students, 2) Student Response Questionnaire, (3) Sheet Observation on the Implementation of Fraction Block Media Usage, and (4) Documentation. Analysis Techniques Data to be used are Analysis of Descriptive and Inferential Data. The Research Results Show That (1) The learning process using Fraction Block media in the experimental class takes place effectively because the percentage categories for each meeting increase. (2) The value of post non test in the experimental class shows that more than 50% of students are in the category of interest. While in the control class more than 50% of students are in the less interested category, (3) The average student response is at an average of 78 with a standard deviation of 5.28 from the ideal score of 100, and (4) There is a positive influence on block media usage Fractions in the learning process.Â Â